The Etiology and Pathogenesis of Chronic Rhinosinusitis: a Review of Current Hypotheses - Lam, Kent (Curr Allergy Asthma Rep, 2015)
Chronic rhinosinusitis (CRS) is a broad clinical syndrome that is characterized by prolonged mucosal inflammation of the nose and paranasal sinuses, and is typically divided into two subtypes based on the presence or absence of nasal polyps. The etiology and pathogenesis of both forms remain areas of active research. Over the last 15 years, a number of hypotheses have been proposed to explain all or part of the clinical CRS spectrum. These hypotheses reflect the concept that CRS results from a dysfunctional interplay between individual host characteristics and factors exogenous to the host. Six broad theories on CRS etiology and pathogenesis are discussed as follows: (1) the “fungal hypothesis,” (2) the “superantigen hypothesis,” (3) the “biofilm hypothesis,” and (4) the “microbiome hypothesis,” all of which emphasize key environmental factors, and (5) the “eicosanoid hypothesis” and (6) the “immune barrier hypothesis,” which describe specific host factors. These theories are reviewed, and the evidence supporting them is critically appraised.